CEU Graduation Ceremony 2002 (edited)
Edited version of the recording of the CEU’s 11th Graduation Ceremony on June 20, 2002. Contains excerpts from the academic procession, the introductory remarks delivered by Yehuda Elkana (President and Rector of CEU), the speeches of the Alumni Speaker and the Student Speaker, fragments of the musical interlude presented by violinist Emese Kapcsos and images of conferring master’s and doctoral degrees. It continues with part of George Soros’ speech and the awarding of the CEU Open Society Prize to Mikheil Saakashvili (former Minister of Justice) and Zurab Zhvania (former Chairman of the Parliament). The edited version continues with Yehuda Elkana reading a letter from Péter Medgyes (Under-secretary of State for International Relations from the Ministry of Culture and Education, Budapest), who could not attend the ceremony. It ends with the moving of the tassels and the academic recessional.